(untitled) (IMC Journal of Medical Science, 2021)
Burkholderia pseudomallei is the etiological agent of melioidosis. It is a gram-negative bacillus present in environment and intrinsically resistant to many antibiotics including aminoglycosides. However, recently aminoglycoside susceptible B. pseudomallei has been isolated from melioidosis cases and reported from some countries of the world. But, such aminoglycoside susceptible B. pseudomallei has never been detected in Bangladesh either from melioidosis cases or from environment. All the B. pseudomallei isolated so far in Bangladesh were resistant to gentamicin and other aminoglycosides. Here, we describe a disseminated case of melioidosis caused by aminoglycoside susceptible B. pseudomallei in a 55 years old Bengali male patient. This is the first case of melioidosis due to aminoglycoside susceptible B. pseudomallei in Bangladesh. Ibrahim Med. Coll. J. 2020; 14(2): 55-59